Nanoparticles as Smart Carriers for Enhanced Cancer Immunotherapy - Thakur, Neelam; Thakur, Saloni; Chatterjee, Sharmistha; Das, Joydeep; Sil, Parames C. (Frontiers in Chemistry, 2020)
Cancer immunotherapy has emerged as a promising strategy for the treatment of many forms of cancer by stimulating body’s own immune system. This therapy not only eradicates tumor cells by inducing strong anti-tumor immune response but also prevent their recurrence. The clinical cancer immunotherapy faces some insurmountable challenges including high immune-mediated toxicity, lack of effective and targeted delivery of cancer antigens to immune cells and off-target side effects. However, nanotechnology offers some solutions to overcome those limitations, and thus can potentiate the efficacy of immunotherapy. This review focuses on the advancement of nanoparticle-mediated delivery of immunomodulating agents for efficient cancer immunotherapy. Here we have outlined the use of the immunostimulatory nanoparticles as a smart carrier for effective delivery of cancer antigens and adjuvants, type of interactions between nanoparticles and the antigen/adjuvant as well as the factors controlling the interaction between nanoparticles and the receptors on antigen presenting cells. Besides, the role of nanoparticles in targeting/activating immune cells and modulating the immunosuppressive tumor microenvironment has also been discussed extensively. Finally, we have summarized some theranostic applications of the immunomodulatory nanomaterials in treating cancers based on the earlier published reports.